Pembelajaran Menulis dengan Metode Interpretasi Siswa Teknik Alat Berat SMK: Writing Learning with Interpretation Method for Heavy Equipment Engineering Students of Vocational High School - Nainggolan, Kristiani (Information Technology and Science(ITScience), 2025)
Writing learning is one of the fundamental language skills in education because writing not only functions as a means of communication but also as a tool to develop students' critical and creative thinking skills. This study examines the effectiveness of the interpretation method in writing learning for students majoring in Heavy Equipment Engineering at SMK Negeri 1 Bunyu. The qualitative approach with an interpretive paradigm is used to understand students' subjective experiences in processing, understanding, and conveying information in writing. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, narrative presentation, and verification with triangulation and member check. The study results showed that applying the interpretation method in matching, completing, and presentation/discussion exercises improved students' abilities in understanding, using, analyzing, and creating according to Bloom's Taxonomy. Students showed a high level of success in understanding the contents of the text (83–88%) but still needed reinforcement in the aspects of analysis and argument development (58–65%). According to Gronlund's theory, the assessment holistically covered cognitive, affective, and psychomotor aspects. Thus, the interpretation method has proven effective in improving the quality of writing learning, which is not only technical but also reflective, contextual, and relevant to the needs of the vocational work world.